RELIGIUSITAS DAN PSYCHOLOGICAL WELL-BEING: PERAN MEDIASI PERILAKU PROSOSIAL PADA MAHASISWA AKTIVIS ORGANISASI IMM - Firdaus, Rahmanil; Hazim, Hazim (Jurnal Psikohumanika, 2023)
This study aims to examine the role of prosocial behavior as a mediator between the relationship between religiosity and psychological well-being in student activist student organizations. The respondents of the study were undergraduate students who participated in the IMM organization at the University of Muhammadiyah Sidoarjo, as well as a sample of 202 students. The sampling technique uses simple random sampling. Research instruments based on the psychological well-being scale of Ryff (1989) (α=741), Prosocial Tendencies Measure-Revised (α=0.792), and the religiosity scale of Stark & Glork (1968) (α=907). Data analysis using mediated path model using JASP 0.17.2.0 software. The results showed that there was a positive relationship between religiosity and psychological well-being (p = 0.045<0.05), and prosocial behavior could partially mediate the relationship between religiosity and psychological well-being in IMM student activists (p = <0.001). This is possible because there are other factors such as internal and external factors that can mediate the relationship.